Radiology of HIV/AIDS A Practical Approach - Li, Hongjun; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book provides a comprehensive overview of modern methodology, diagnostic methods and techniques of HIV/AIDS imaging. It starts with a general review of HIV/AIDS imaging and evidence based medicine (EBM). In the following chapters, authors introduce 13 of most common types of AIDS/HIV-associated diseases separately. High-quality examples combined with computed tomography (CT), Magnetic resonance imaging (MRI), gross anatomy and pathology images are clearly illustrated. Moreover, the use of functional imaging in HIV/AIDS diagnosis and differential diagnosis is an essential part that diagnostic doctors will find to be useful. Li Hongjun, is professor and director of the diagnostic radiology department in Beijing You An Hospital, affiliated with Capital Medical University, Beijing, China.
Molecular Biology of HIV/AIDS and Its Clinical Management -- An Overview of Clinical Immunology of HIV/AIDS -- An Overview of Clinical Microbiology of HIV/AIDS -- Epidemiological Investigation of AIDS -- Pathogenetic and Pathological Mechanism -- Clinical Manifestations of HIV/AIDS Infection -- Laboratory Test and Special Examinations -- Diagnostic Imaging -- AIDS Imaging and Evidence Based Medicine -- Clinical Medication Against HIV/AIDS -- Introduction to Assessment and Monitoring of Critical AIDS -- HIV Related Effect Factors -- HIV/AIDS Related Nervous System Diseases -- HIV/AIDS Related Myeleterosisand Peripheral Neuropathy -- HIV/AIDS Related Eye Diseases -- HIV/AIDS Related Neck Diseases -- HIV/AIDS Related Respiratory Diseases -- HIV/AIDS Related Cardiac Diseases -- HIV/AIDS Related Gastrointestinal Diseases -- HIV/AIDS Related Hepatobiliary, Pancreatic and Splenic Diseases -- HIV/AIDS Related Peritoneal and Retroperitoneal Disease -- HIV/AIDS Related Urogenital Disease -- HIV/AIDS Related Musculoskeletal Diseases -- HIV/AIDS Related Pediatric Diseases -- HIV/AIDS Related Skin Diseases -- Functional Imaging of HIV/AIDS.
Keywords: Medicine; Radiology, Medical; Emerging infectious diseases; Pathology; Medicine & Public Health; Diagnostic Radiology; Infectious Diseases; Pathology